The Moderating Effect of Religiosity on Fashion Uniqueness and Consciousness in Halal Fashion Purchase - Yudha, Ana Toni Roby Candra; Huda, Nurul; Maksum, Maksum; Sherawali, Sherawali; Wijayanti, Ida (UIN Sunan Gunung Djati Bandung, 2024)
The Islamic fashion model in Indonesia continues to evolve in line with the increasing Muslim population. However, there is limited research on consumer perceptions and the role of religiosity in the context of halal fashion products. This research aims to investigate the influence of fashion uniqueness and consciousness on halal fashion purchase behavior with religiosity as a moderating variable. Halal fashion in this research emphasizes halal product standards in fashion. This research used a quantitative approach through a survey targeting Millennials and Gen Z individuals. A total of 186 respondents were obtained, deemed valid and complete. Additionally, this study used SemPLS-3 to validate hypotheses and evaluate the model. This analysis is considered appropriate as it can test several variable relationships simultaneously or in multivariate analysis. The findings of this study show that halal fashion purchase behavior is influenced by fashion uniqueness and consciousness. Both factors have a positive influence on halal fashion purchase behavior. However, religiosity does not impact halal purchase behavior, nor does it moderate the role of fashion uniqueness and consciousness variables on halal purchase behavior. It suggests that decisions to purchase halal fashion are more influenced by fashion uniqueness and awareness of its halal status rather than individual religiosity levels. This research highlights the need for a deeper understanding of consumer behavior in relation to religiosity and halal fashion, contributing to the fields of economics and social sciences.